Barriers and opportunities for implementing prevention of mother to child transmission (PMTCT) in Bangli District - Ketut Espana Giri; Ni Made Sri Nopiyani; Ketut Tuti Parwati Merati (Public Health and Preventive Medicine Archive, 2017)
Background and purpose: HIV testing among pregnant women can reduce the risk of mother to child HIV transmission. The implementation of prevention of mother to child transmission (PMTCT) program in Bangli District is suboptimal. This study aims to explore challenges and opportunities for implementing PMTCT program from both user and provider perspectives. Methods: A qualitative approach was conducted in Bangli District between April and May 2016. Data were collected using in-depth interviews with 18 informants. All informants were purposively selected and covered of 10 pregnant women, two counsellors, two laboratory analysts, two head of public health centres, one disease control officer from Bangli District Health Office and one officer from Bangli District AIDS Commission. Data were analysed using thematic method. Results: Pregnant women chose to have ANC service at private midwife and obstetrician instead of public health centre. From health providers’ perspectives barrier of PMTCT implementation included lack of health human resources and a high level of stigma and discrimination related to HIV/AIDS in the community. This study revealed that there was an opportunity for PMTCT implementation in Bangli District due to positive attitudes and supports from husband and health provider toward HIV testing. Another opportunity is toinvolve village health cadres and community leaders in promoting HIV testing among pregnant women. Conclusions: Implementation of PMTCT program in health centre should include network of private practitioner and enhance village health cadres’ and community leaders’ participation.